Identification of giant Mimivirus protein functions using RNA interference - Sobhy, Haitham; Scola, Bernard La; Pagnier, Isabelle; Raoult, Didier; Colson, Philippe (Frontiers in Microbiology, 2015)
Genomic analysis of giant viruses, such as Mimivirus, has revealed that more than half of the putative genes have no known functions (ORFans). We knocked down Mimivirus genes using short interfering RNA (siRNA) as a proof of concept to determine the functions of giant virus ORFans. As fibers are easy to observe, we targeted a gene encoding a protein absent in a Mimivirus mutant devoid of fibers as well as 3 genes encoding products identified in a protein concentrate of fibers, including one ORFan and one gene of unknown function. We found that knocking down these four genes was associated with depletion or modification of the fibers. Our strategy of silencing ORFan genes in giant viruses opens a way to identify its complete gene repertoire and may clarify the role of these genes, differentiating between junk DNA and truly used genes. Using this strategy, we were able to annotate 4 proteins in Mimivirus and 30 homologous proteins in other giant viruses. In addition, we were able to annotate >500 proteins from cellular organisms and 100 from metagenomic databases.